Affine projection sign algorithm based control for mitigation of distribution side power quality problems. Issue 2 (10th May 2021) - Sharma, Archana; Rajpurohit, Bharat Singh; Agnihotri, Samar
Abstract: This paper proposes the implementation of Affine Projection Sign Algorithm (APSA) based control for DSTATCOM to mitigate distribution side power quality issues like harmonic elimination, reactive power compensation, load balancing, power factor compensation, voltage regulation, etc. Affine projection algorithms have already finds application in power quality mitigation, but they suffer from high complexity and degraded performance due to impulsive interference. Whereas, sign algorithms are known to be robust against the impulsive noise and converges faster. Hence, sign algorithm with affine projection is proposed for mitigation of power quality problems in this work. APSA is used to estimate the reference active and reactive power component of polluted load current, which is further used to generate the reference signal for DSTATCOM. The performance of the algorithm is investigated for some real operating conditions of power system network in MATLAB/SIMULINK environment. The algorithm is tested in real‐time simulator for validation. The result shows that the control algorithm is able to resolve distribution side power quality problems with fast convergence.